2019
DOI: 10.1016/j.amjcard.2018.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Mortality in Patients With Coronary Artery Disease

Abstract: Extremes in sleep duration are associated with higher cardiovascular risk in the general population, but their impact in patients with documented coronary artery disease (CAD) remains unknown and potentially of clinical significance. We hypothesized that both short and long sleep duration are associated with higher mortality in CAD. We inquired about sleep durations in 2,846 patients enrolled in the Emory Cardiovascular Biobank (mean age 64 years, 38% female, 23% Black, and 82% with obstructive CAD, defined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 28 publications
0
29
2
Order By: Relevance
“…Very little data is available regarding the relationship between sleep duration and cardiovascular events in patients with confirmed cardiovascular disease. Kim et al recently analysed the relationship between sleep duration and risk of events in about three thousand patients with confirmed coronary artery disease included in the “Emory Cardiovascular Biobank” [ 9 ]. Short or long sleep duration has been associated with a significant increase in the risk of death from all causes during an average follow-up of 2.8 years.…”
Section: Sleep Disorders and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little data is available regarding the relationship between sleep duration and cardiovascular events in patients with confirmed cardiovascular disease. Kim et al recently analysed the relationship between sleep duration and risk of events in about three thousand patients with confirmed coronary artery disease included in the “Emory Cardiovascular Biobank” [ 9 ]. Short or long sleep duration has been associated with a significant increase in the risk of death from all causes during an average follow-up of 2.8 years.…”
Section: Sleep Disorders and Cardiovascular Diseasesmentioning
confidence: 99%
“…In addition, the expression of more than 700 genes involved in multiple functions, including metabolic control and redox status, is modified by sleep deprivation [4,8]. In parallel, a U-shaped association between sleep duration and all-cause mortality as well as increased cardiovascular risk has been described [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has recently shown that both short and long sleep duration is associated with higher all-cause mortality in both Blacks and non-Blacks with CAD. 60 Future studies are needed to investigate whether higher rates of sleep disturbances among Black adults with MI translate into worse future outcomes. Strengths of this study include the comprehensive phenotyping of both cases and controls across multiple levels, including sociodemographic, medical and psychosocial data, which allowed us to investigate the role of all these factors on racial disparities in sleep.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies examined the overlapping sleep duration for a lower risk of acquiring them. While new papers have been published on this subject in the past 5 years, the findings were inconsistent (4)(5)(6)(7)(8)(9)(10)(11)(12). Thus, through meta-analysis, this research seeks to revise the association of sleep duration with CCDs and unveil the sleep duration range valuable to preventing these diseases.…”
Section: Introductionmentioning
confidence: 99%